ANALISIS PERTUMBUHAN DAN HASIL TANAMAN JABON (Anthocephallus cadamba) - . Wahyudi (PERENNIAL, 2012)
Anthocephallus cadamba was a native species and one of some commercial trees which had a good prospect to develop on the low production forest. This research was aimed to analyze growth and yield of A. cadamba plantation, including the living trees percentage, productivity, economic cutting cycle, and its profit. Parameter of data analysis used trees diameter, high and volume, mean annual increment, polynomial equation modelling and financial analysis i.e. net present value (NPV), and benefit cost ratio (BCR). The research had been conducted at research plots of A. cadamba in sub District of Mandau Talawang, Central Kalimantan Province since 1998 to 2010. Soil type in the site was ultisol former shifting cultivation and scrubs. The result of this research showed that living trees precentage at 12 years old was 57.7 %. Mean annual increment and its density were 19.05 m3 ha-1 and 641 tree ha-1 respectively. Equation modelling of jabon plantation was y = 4.7814 + 3.6028x - 0.185x2 (R2= 63.34 %). In the bank rate of 9 % year-1, the economic cutting cycle of this plantation was 13 years with net present value was IDR 72,79 million per ha. If the bank rate of 6 % and 12 % per year, then net present value at the 13 years were IDR 108.52 and IDR 48.56 million ha-1 respectively. The A. cadamba was suitable to timber estate and to increase the productivity of former shifting cultivation, scrub, and low potential forest areas. Key words: growth and yield, mean annual increment, Anthocephallus cadamba, economic cutting cycle